The Influence of Teachers’ Work Motivation on the Learning Quality in Public Elementary School in Sumber District, Rembang Regency - Ahmad Agus Alim; Ali Shodiqin; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
Primary education plays a vital role in shaping human resource quality and long-term educational outcomes. This study examines the effect of teachers’ work motivation on learning quality in public elementary schools in Sumber District, Rembang Regency. Learning quality is essential for developing students’ cognitive, affective, and psychomotor competencies. However, recent reports indicate fluctuations and declines in several aspects of learning quality, highlighting the need to identify contributing factors. This research used a quantitative ex post facto design with a sample of 75 teachers selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and regression analysis. The findings reveal that teachers’ work motivation has a positive and significant effect on learning quality, with a strong correlation and substantial contribution. Highly motivated teachers tend to demonstrate better lesson planning, more innovative teaching practices, and more consistent assessment. In conclusion, teachers’ work motivation is a key factor influencing learning quality, and strengthening both intrinsic and extrinsic motivation is essential to improve teaching effectiveness and sustain primary education quality.